The Linguistic Significance Of The Terms And Styles Of Human Dignity In The Holy Quran: The Era Of Pharaoh As A Case Study/ الدلالة اللغوية لألفاظ الكرامة الإنسانية وأساليبها في القرآن الكريم: عهد فرعون أنموذجا - Yaseen Taha Othman Shihab Al-Hiti; Qassim Saleh Ali Kuba’ Al-Ani (Ijaz Arabi Journal of Arabic Learning, 2026)
This research aims to study the significance of terms related to human dignity in the Holy Qur’an by examining the era of Pharaoh as a case study. A set of verses depicting Pharaoh’s practices against the Children of Israel were analyzed. The study shows that the Qur’an employs terms with strong connotations to express violations of dignity, such as yastad’if (to oppress), yadhbah (to slaughter), yastahyi (to spare women), and ya‘lu fi al-ard (to exalt oneself in the land), while simultaneously highlighting values of justice, deliverance, and empowerment as manifestations of restoring dignity. The findings also indicate that the linguistic structure of the verses contributes to reinforcing awareness of the gravity of tyranny and its impact on crushing human beings, and conversely reflects a comprehensive Qur’anic vision for preserving human dignity. The research concludes that the Holy Qur’an, through the story of Pharaoh, presents an integrated model of the violation of human dignity, employing precise terms with profound semantic dimensions that reveal the nature of tyranny and its destructive effects on the individual and society. The study also highlights that the restoration of dignity is linked to faith, justice, and resistance to oppression